2019
DOI: 10.29122/jtl.v20i2.3547
|View full text |Cite
|
Sign up to set email alerts
|

Distribusi Spasial, Sumber Pencemaran, dan Kajian Risiko Ekologi Polisiklik Aromatik Hidrokarbon (PAH) dalam Sedimen Pesisir di Pulau Bintan, Indonesia

Abstract: Bintan Island is the small island in the Riau Archipelago which borders Singapore and Malaysia. Its water is crossed by international shipping lines. Therefore, water quality in this area is potentially polluted by marine activities. The present study aimed to evaluate the concentration, spatial distribution, and assessment of ecological risks of polycyclic aromatic hydrocarbons (PAHs) in surface sediments from selected coastal water of Bintan. Surface sediments in this study were extracted by using the ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
1
3
0
1
Order By: Relevance
“…Conversely, benzo[k]fluoranthene, benz[a]anthracene, and pyrene demonstrated higher bioaccumulation levels in the sediments. The compounds detected in these sediments closely resemble those found in Bintan Island, as documented in a previous study [14]. The bioaccumulation of Polycyclic Aromatic Hydrocarbons (PAHs) in simping scallop (Placuna placenta) has undergone significant development, mainly due to anthropogenic activities such as industrial operations, human settlements, and land-based sources that have the potential to impact water quality.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…Conversely, benzo[k]fluoranthene, benz[a]anthracene, and pyrene demonstrated higher bioaccumulation levels in the sediments. The compounds detected in these sediments closely resemble those found in Bintan Island, as documented in a previous study [14]. The bioaccumulation of Polycyclic Aromatic Hydrocarbons (PAHs) in simping scallop (Placuna placenta) has undergone significant development, mainly due to anthropogenic activities such as industrial operations, human settlements, and land-based sources that have the potential to impact water quality.…”
Section: Resultssupporting
confidence: 78%
“…In a separate study [14], researchers found that the sediments in Bintan Island waters exhibited different characteristics for each type of PAHs. Naphthalene, fluorene, and anthracene, with two or three benzene rings in a linear arrangement, were classified as Low Molecular Weight (LMW) compounds.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Hasil kalibrasi kurva standar ∑PAH-16 dengan variasi konsentrasi 10, 100, 500, dan 1000 ng.g 1didapatkan nilai R 2 masing senyawa ∑PAH-16 yaitu naphthalene, 2bromonaphthalene, acenaphthene, acenaphthylene, fluorene, phenanthrene, anthracene, fluoranthene, pyrene, benzo (a) anthracene, chrysene, benzo (k) fluoranthene, benzo (a) pyrene, indeno (1,2,3-cd) pyrene, dibenzo (ah) anthracene, dan benzo (ghi) perylene adalah > 0,90. Standar internal jenis naphthalene-d8, acenaphthene-d10, phenanthrene-d10, dan chrysene-d12 diinjeksikan dalam sampel sebelum analisis di instrumen GCMS (Yogaswara et al, 2019). Sampel blanko digunakan sebagai kontrol dan koreksi terhadap hasil yang didapat.…”
Section: Kendali Mutuunclassified